1987
DOI: 10.1107/s0108767387098490
|View full text |Cite
|
Sign up to set email alerts
|

A multisolution procedureviatendentially maximally entropical starting sets

Abstract: Large starting sets of random phases are in general inconsistent with positivity and atomicity of the electron density. A correct solution can be achieved from them because the tangent formula is a process which maximizes entropy under physical constraints involving the positivity and atomicity of electron density. Starting sets which are themselves tendentially maximally entropical can be created by associating phase shifts A, generated according to the yon Mises distribution of each triplet phase, to some (f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Only four structures remain unsolved by SIR [however, it cannot be concluded that SIR is unable to solve those structures using non-default conditions; see for example, Burla, Giacovazzo & Polidori (1987)]. Very often the ratio (number of correct solutions/number of trials) is larger in PROT 2 than in PROT 1.…”
Section: Experimental Results and Conclusionmentioning
confidence: 99%
“…Only four structures remain unsolved by SIR [however, it cannot be concluded that SIR is unable to solve those structures using non-default conditions; see for example, Burla, Giacovazzo & Polidori (1987)]. Very often the ratio (number of correct solutions/number of trials) is larger in PROT 2 than in PROT 1.…”
Section: Experimental Results and Conclusionmentioning
confidence: 99%